(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Based on the study conducted, it was discovered that individuals who are incarcerated and then released back into society, commonly known as ex-offenders, face many obstacles during the process. The study aims to evaluate the level of community integration of ex- convicts in Brgy. Nagka-Isang Nayon, Novaliches Quezon City, mainly in terms of their financial and work-related situations. Ex-convicts face many challenges, such as social exclusion, maltreatment, aggression, stress, and anxiety, which affect their physical, psychological, and social well-being. The results of this research have the potential to form a solid foundation for future studies on ex-offenders difficulties in reintegrating themselves into society. Additionally, it expedites the identification of issues and potential fixes for better prison management. Every prisoner who is prepared and willing to change is also given the same treatment. Even yet, there are still restrictions depending on the seriousness of the crime and transgression committed by the prisoner. The recommended steps suggested in this study can also assist policymakers in the creation of specific programs and policies that aid ex-offenders in their efforts to re-enter the community. Through this, the government can help offenders find their place in society and contribute to its growth without causing trouble to anyone.